2006
DOI: 10.1124/jpet.106.108084
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of AT1- and AT2-Receptors by Higher Concentrations of Angiotensin II in the Smooth Muscle Cells of Rat Internal Anal Sphincter

Abstract: Previous studies have reported bimodal effects by angiotensin II (Ang II) in the rat internal anal sphincter (IAS), a concentrationdependent contraction (at lower concentrations) and relaxation (at higher concentrations). The experiments suggest the abovementioned responses are the result of Ang II subtype I receptor(s) (AT 1 -R) and subtype II receptor(s) (AT 2 -R) activation, respectively. These studies determined the role and mechanism of AT 2 -R-induced relaxation of the smooth muscle cells (SMCs) from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…In addition, our observations regarding the functional role of ATBP -i.e., a protein necessary for transport as well as function of the AT 2 receptor -are consistent with two recent publications. Work of de Godoy and Rattan indicates that the externalisation of the AT 2 receptor from an intracellular localisation to the plasma membrane may be responsible for receptor activation 43 which is consistent with observations of Miura et al suggesting that AT 2 receptor translocation in the cell membrane is necessary for cell signalling. 30 Apart from the signal transduction cascades downstream of the AT 2 receptor linked to direct physical interactions, our group was able to show that AT 2 receptor activation regulates the mRNA level of the zinc finger homoeodomain enhancerbinding protein (Zfhep).…”
supporting
confidence: 79%
“…In addition, our observations regarding the functional role of ATBP -i.e., a protein necessary for transport as well as function of the AT 2 receptor -are consistent with two recent publications. Work of de Godoy and Rattan indicates that the externalisation of the AT 2 receptor from an intracellular localisation to the plasma membrane may be responsible for receptor activation 43 which is consistent with observations of Miura et al suggesting that AT 2 receptor translocation in the cell membrane is necessary for cell signalling. 30 Apart from the signal transduction cascades downstream of the AT 2 receptor linked to direct physical interactions, our group was able to show that AT 2 receptor activation regulates the mRNA level of the zinc finger homoeodomain enhancerbinding protein (Zfhep).…”
supporting
confidence: 79%
“…Vascular prostaglandin synthesis is induced by Ang II [56], whereas prostaglandin E2 has been found to counteract the effect of Ang II on activation of NADPH oxidase and vasoconstriction in a mouse model [57]. In addition, high Ang II concentrations may result in agonist-induced receptor internalization and/or desensitization [58,59]. This may also explain the moderate effect of Ang II on myometrium protein synthesis/hypertrophy seen in the current model.…”
Section: Discussionmentioning
confidence: 71%
“…In an elegant follow-up study on rat internal anal sphincter, de Godoy and Rattan demonstrated that internalisation of AT 1 receptors and externalisation of AT 2 receptors may be responsible for the activation of the AT 2 receptors, which leads to the relaxation at higher concentrations of Ang II. 18 As the internalisation/externalisation behaviour depends on Ang II receptor activation, it is an important issue to consider when judging effects of Ang II and related receptor ligands. It is obvious that the role of AT 2 receptors on myenteric neurons in the GI tract needs further investigation.…”
Section: Gi Wall Musculaturementioning
confidence: 99%